Dynamic Moves Found in The Classroom Discourse - Handayani, Rinda Maripah; Hartini, Nurani (Universitas Swadaya Gunung Jati, 2016)
Interaction is an important word for language teacher. The interaction between teacher and students can determine the quality of teaching learning. In some instances of classroom interaction, the occurrences of dynamic moves cannot be avoided. The dynamic elements are always found in the interaction between teacher and students. In this case, teacher plays significantrole in the classroom interaction. In the scope of this phenomenon, the research was aimed to find out types of dynamic moves in the classroom interaction and to reveal how question and answer are realized. The data were gathered from the Efl classroom interaction which was recorded. The findings revealed that varieties of dynamic moves were found in the interaction. These findings are interesting to be discuss among efl teachers so that the English teachers are able to boost their instructional practices.